Effect of Drawing Pass on Softening or Plasticizing of Q235 Steel Bar during Electrochemical Cold Drawing - Jangli Guo; Tijun Chen; Bo Li (Metals, 2020)
In this work, the effect of drawing pass on the surface layer softening or plasticizing of Q235 steel bar during electrochemical cold drawing (ECD) was studied, as well as cold drawing in air (DIA) for comparison. The results indicate that the softening or plasticizing degree gradually decreases with increasing drawing pass. The reason for this should be that dislocations generated in surface layer are only partially overflowed from the surface in the form of additional dislocation flux. The general dislocation density thereby gradually increases with the increase in drawing pass, resulting in the increase in the work hardening degree of the surface layer, and thus, the drawing stress. In this case, the texture orientation of the bar surface layer is gradually enhanced. In contrast, the dislocation density, and thus the work hardening degree of DIA bar, are higher than those of the ECD partner, resulting in larger drawing stress. ECD can obtain a product with excellent comprehensive mechanical properties compared with DIA, and there are no cracks on the fracture surface of ECD bar drawn for at least seven passes.